In Vitro Studies on Nasal Formulations of Nanostructured Lipid Carriers (NLC) and Solid Lipid Nanoparticles (SLN) - Cláudia Pina Costa; Sandra Barreiro; João Nuno Moreira; Renata Silva; Hugo Almeida; José Manuel Sousa Lobo; Ana Catarina Silva (MDPI AG, 2021)
The nasal route has been used for many years for the local treatment of nasal diseases. More recently, this route has been gaining momentum, due to the possibility of targeting the central nervous system (CNS) from the nasal cavity, avoiding the blood−brain barrier (BBB). In this area, the use of lipid nanoparticles, such as nanostructured lipid carriers (NLC) and solid lipid nanoparticles (SLN), in nasal formulations has shown promising outcomes on a wide array of indications such as brain diseases, including epilepsy, multiple sclerosis, Alzheimer's disease, Parkinson's disease and gliomas. Herein, the state of the art of the most recent literature available on in vitro studies with nasal formulations of lipid nanoparticles is discussed. Specific in vitro cell culture models are needed to assess the cytotoxicity of nasal formulations and to explore the underlying mechanism(s) of drug transport and absorption across the nasal mucosa. In addition, different studies with 3D nasal casts are reported, showing their ability to predict the drug deposition in the nasal cavity and evaluating the factors that interfere in this process, such as nasal cavity area, type of administration device and angle of application, inspiratory flow, presence of mucoadhesive agents, among others. Notwithstanding, they do not preclude the use of confirmatory in vivo studies, a significant impact on the 3R (replacement, reduction and refinement) principle within the scope of animal experiments is expected. The use of 3D nasal casts to test nasal formulations of lipid nanoparticles is still totally unexplored, to the authors best knowledge, thus constituting a wide open field of research.